Pengaruh Digital Marketing, Celebrity Endorser dan Gaya Hidup Terhadap Keputusan Pembelian Pada Tokopedia - Dede Alipudin; Edy Nursanta; Siti Masitoh (Forum Kerjasama Pendidikan Tinggi, 2023)
Technological developments currently have very rapid progress, including in the fields of economics and marketing. The internet is an information mechanism that provides advice or facilities to obtain important data needed. With advances in the field of information and communication innovation, it feels like the world no longer has boundaries, distance and time. Utilization for business people does not need to experience difficult things in collecting various data to support their business operations. Even today, various types of business information can be obtained quickly and without problems, so the data obtained needs to be filtered to get accurate and significant data. The method of analysis in this study used quantitative primary data, the test stages carried out were validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, coefficient of determination, t-test and F-test. The data used in this study used a questionnaire instrument, and valid data collected by 111 respondents. The sampling method in this study was purposive sampling. The testing tool used is SPSS version 29. The results of the study show that the Celebrity Endorser and Lifestyle variables partially influence the Purchase Decision at Tokopedia. Meanwhile, Digital Marketing variables do not partially influence Purchase Decisions at Tokopedia, and Digital Marketing, Celebrity Endorser, and Lifestyle variables simultaneously influence Purchase Decisions at Tokopedia.